Yowamushi pedal. 13 - Watanabe, Wataru, 1971- (Yen Press, 2020)
With less than five kilometers remaining on the grueling climb up Mt. Fuji, the challenge between Manami and Midousuji comes to a close as the battle for the finish line begins! Midousuji breaks away, but Sohoku's Imaizumi relentlessly pursues him. Will Imaizumi's battle with his long-standing rival end in victory-or defeat?